Women's labor supply: a cross-country study - Altarawneh, Yaseen Mamdouh, author; Fan, Chuen-Mei, advisor (Colorado State University. Libraries, 2007)
This study aims at analyzing the cross-country variations in women's participation rates (WPRs) and the gender-gap in economic activity. It covers 45 countries over 1970-2002, 15 countries from each group: low income countries (LICs), middle income countries (MICs), and high income countries (HICs). The study employs the Seemingly Unrelated Regression Model in conjunction with the Fixed Effects Model to guarantee the individuality of each country and to control for spatial autocorrelation. Several factors such as GDP growth, GDP/capita, education, fertility, urbanization, government's role, and cultural factors are used as explanatory variables.

The empirical work confirms the main hypothesis that cross-country variations in WPRs are attributed to the inter-group variations in average characteristics (mean values of explanatory variables) and to the inter-group variations in women's participation behavior (the responsiveness of women's participation to the change in characteristics). Furthermore, the results reveal that gender-gaps in education and in earned income are major sources for the gender-gap in economic activity.

Common findings in all models regarding the positive impact of education and favorable cultural factors on WPRs, while the impact of other suggested variables on WPRs varies according to the stage of economic development i.e. GDP growth rate reveals a negative impact-dominance of "added worker effect"- in MICs and a positive impact-dominance of "discouraged worker effect"- in LICs and HICs. The fertility rate (ratio of population <15 was used as proxy) has shown a negative impact only in HICs and MICs. Moreover, GDP/capita and urbanization reveal a positive impact on WPRs only in HICs and MICs supporting the hypothesis of over-urbanization in LICs. Accordingly, the suggested U-shaped relationship between GDP/capita and WPRs has been proven only in HICs. The government's role reveals a positive impact only in HICs.

Apparently, despite the progress that Jordanian women have made in education, their participation rates are relatively low compared to the average MICs. The study provides some explanations for this puzzle, i.e. the high unemployment rate has a discouraging effect among women, the demographic characteristics are very restrictive for more women's participation, and the high influence of cultural factors is limiting women's job opportunities.
Keywords: earned income; gender gap; labor supply; women; women; regression analysis; academic achievement; studies; gender differences; population; trends; families and family life; expenditures; age; participation; leisure; decision making; variables; copyright; preschool education; family income